Development and Validation of a Hemostatic Activity-Based Learning Video on the Cir-culatory System for High School Biology Education - Irma Naura Rifanka; Ruqiah Ganda Putri Panjaitan; Andi Besse Tenriawaru; Liangyue Li (Universitas Muhammadiyah Surakarta, 2025)
The rapid advancement of technology enables the development of technology-based learning media that can visualize concepts clearly, such as learning videos. These videos can be developed based on various sources, including research findings. Therefore, this study aims to develop a learning video on the topic of the circulatory system for high school students in the eleventh grade, based on the hemostatic activity test of sungkai leaves extract (Peronema canescens Jack.). The development process follows the Research and Development (R&D) approach, which includes analyzing potential issues, gathering information, designing the product, validating the design, making improvements, and producing the final product. The video contains nine learning objectives organized into five sessions. The validity of the learning video is assessed based on four aspects: format, content, linguistic, and presentation. According to the validation results from the validators, all aspects received a very valid rating, with average scores of 0.96 for format, 0.95 for content, 0.93 for linguistic, and 0.95 for presentation. Overall, the average score for all four aspects is 0.95, indicating a very valid rating. This suggests that the developed video is suitable for use as a learning media.